NUCLEAR POWER IN PAKISTAN - Siddiqui, Zia H.; Qureshi, I. H. (The Nucleus, 2020)
Pakistan started its nuclear power program by installing a 137 MWe Canadian Deuterium Reactor (CANDU) at Karachi in 1971 which became operational in 1972. The post-contract technical support for the Karachi Nuclear Power Plant (KANUPP) was withdrawn by Canada in 1976 as a consequence of Indian nuclear device test in 1974. Inspite of various difficulties PAEC resolved to continue to operate KANUPP and started a process for the indigenous fabrication of spare parts and nuclear fuel. The first fuel bundle fabricated in Pakistan was loaded in the core in 1980. Since then KANUPP has been operating on the indigenously fabricated fuel. The plant computer systems and the most critical instrumentation and Control systems were also replaced with up-to date technology. In 2002 KANUPP completed its original design life of 30 year. A program for the life extension of the plant had already been started. The second nuclear power plant of 300 MWe pressurized water reactor purchased from China was installed at Chasma in 1997, which started commercial operations in 2001. Another unit of 300 MWe will be installed at Chashma in near future. These nuclear power plants have been operating under IAEA safeguards agreements. PAEC through the long-term performance of the two power plants has demonstrated its competence to safely and successfully operate and maintain nuclear power plants. Pakistan foresees an increasingly important and significant share of nuclear power in the energy sector. The Government has recently allocated a share of 8000 MW for nuclear energy in the total energy scenario of Pakistan by the year 2025.